Isolation and Characterization of Cellulolytic Bacteria from Bonoloyo, Cemetery - Risnasari, Wanda Datik; Tyastuti, Erma Musbita; Sidiq, Yasir; Rahayu, Triastuti (Universitas Muhammadiyah Surakarta, 2023)
A public cemetery (TPU) is land provided by the government to bury bodies. The culture of funerals in Indonesia is varied but generally involves being buried in the soil with wrapped clothes, covered wooden boards, and tombs. The material contains cellulose that will be broken down by cellulolytic microorganisms, including bacteria. The exploration of the cellulolytic bacteria of TPU in Indonesia has not been carried out, so this study aims to investigate and identify cellulose bacteria isolates from TPU. This research is a non-experimental study for the isolation of bacteria in the soil of TPU Bonoloyo, Surakarta. A selection of cellulite bacteria is grown in CMC media. Isolates that show cellulolytic activity are identified by observing colonial morphology and Gram coloring. Selection results of cellulolytic bacteria obtained isolates with cellulolytic index (IS) including a high category of 1 isolate (B14), a medium category of 3 isolates (B16, B27, and B45), and 9 low category isolates. The study concluded that 28.8 % showed cellulolytic activity with irregular morphological forms of white dyeing on flat surfaces with flat edges and dominated by gram-negative coccyx-shaped.